A theoretical study of the monolayer-protected gold cluster Au317(SR)110. Issue 15 (4th April 2022) - Li, Lanyan; Wang, Pu; Pei, Yong
Abstract : An unprecedented gold cluster, Au317 (SR)110, containing a 267-atom icosahedral core is theoretically predicted. Based on the DFT and TD-DFT calculation results, the Au317 cluster processes good structural stability and metallic property. Abstract : Significant efforts have been made to uncover the structures of monolayer-protected gold nanoclusters. However, the synthesis, crystallization, and structural analysis of gold nanoclusters with over 300 metal atoms is a grand challenge. In this work, a new gold nanocluster containing 317 gold atoms and 110 thiolate (SH) ligands (referred to as Au317 (SH)110 ) is theoretically studied, which is larger in size than the formerly reported Au279 (SR)84 cluster. The stability of the Au317 (SH)110 cluster is studied based on calculations of the averaged cluster formation energy ( E ave ), indicating that Au317 (SH)110 has good structural stability and that the SPhCOOH ( p -MBA) ligand is a good candidate for stabilizing the cluster. The calculation of density of state and the time-dependent density functional theory (TD-DFT) calculations of the optical absorption properties show that Au317 (SH)110 is in a metallic state.